Will the data markets necessarily fail? A position paper - Pekka Nikander; Tommi Elo (International Telecommunications Society (ITS), 2019)
With the billions of Internet of Things devices connected via the 5G and other networks, loads of useful data are produced. However, the majority of these data are disappearing into the silos of cloud and IoT companies. This problem is exacerbated by the current economic system creating perverse incentives that push companies to keep their data private and not to sell or share them. From the society point of view, this leads to severe inefficiencies. More structurally, Adam Smith's invisible hand does not work: in the data markets, the public and private interests are not aligned by the current market forces. Based on these observations, we present a conjecture wherein we state that any attempts to fix the market failure in the data markets within the current economic structures are bound to be inefficient. Only by redefining fundamental economic concepts, such as ownership and money, we can efficiently align the interests, clear the markets, and gain welfare potential. Furthermore, we briefly suggest an urban community currency experiment wherein this conjecture could be empirically tested.
Keywords: 330; 5G; data markets; market failure; non-rival; anti- rival; creative destruction; perverse incentives